Etymological Resonances between Hebrew and Arabic in the Aptronyms of the Qur’an: Uncovering I‘jāz Lughawī through a Symmetrical Analysis of Meaning - M. Afif Wafiudin; Abu Bakar; Moh Yardho (Journal of Islamic and Occidental Studies, 2026)
This study aims to explore the phenomenon of linguistic miracle (i‘jāz lughawī) identified through a cross-linguistic approach, specifically between Hebrew and Arabic. Both languages share a common genealogical origin, thereby enabling profound semantic and etymological connections. This phenomenon is evident when the Qur’an mentions the names of figures from the Hebrew tradition, forming a unique semantic relationship through an aptronym, namely a name that reflects the characteristics or narrative of its bearer. This study focuses on three main questions: how does the phenomenon of aptronyms manifest in the names of Qur’anic figures, how do Hebrew–Arabic etymological resonances reveal the miraculous dimension of language, and what are the implications? Using a qualitative-comparative linguistic approach and based on a literature review, cross-linguistic aptronymic patterns were identified in several figures: Zakariyā with the phrase dhikr, Isḥāq with the phrase ḍaḥikat, Ya‘qūb with the phrase warā’, Yaḥyā with the phrase ḥanānā, and Ibrāhīm with the phrase abī. These findings indicate the presence of etymological resonance that cannot be attributed to mere linguistic coincidence, but rather constitutes a manifestation of the miraculous nature of the Qur’anic language. This study makes a new contribution to Qur’anic exegesis through a linguistic-comparative approach, whilst opening avenues for further research into etymological relationships among Semitic languages in revelatory texts.